Factor IX inhibitors in haemophilia B: A report of National Haemophilia Registry in China. Issue 1 (26th September 2022) - Dou, Xueqing; Zhang, Wenhui; Poon, Man‐Chiu; Zhang, Xinsheng; Wu, Runhui; Feng, Xiaoqin; Yang, Linhua; Cheng, Peng; Chen, Shu; Wang, Ying; Zhou, Hu; Huang, Meijuan; et al.
Abstract: Introduction: The development of inhibitors against factor FIX (FIX) is the most serious complication of FIX replacement therapy in haemophilia B (HB) patients. Currently, only few cohorts of HB inhibitor patients have been reported worldwide. Aim: This Chinese nationwide study of HB inhibitor patients explored their risk factors for FIX inhibitor development and experience on their management. Methods: We retrospectively analysed patient characteristics, F9 genotypes, treatment strategies and outcomes of HB inhibitor patients registered to the Chinese National Registry and Patient Organization Registry. Results: Forty‐four unique HB inhibitor patients were identified in 4485 unique HB patients registered by year 2021 to the two Registries. Inhibitor diagnosis were usually delayed and the low prevalence (.98%) may suggest some inhibitor patients were not identified. Their median age at inhibitor diagnosis was 7.5 (IQR, 3.0–14.8) years. Most patients (95.5%) had high‐titre inhibitors. Allergic/Anaphylactic reactions occurred in 59.1% patients. Large deletions and nonsense mutations were the most common F9 mutation types in our FIX inhibitor patients. Patients with large F9 gene deletions were more likely to develop inhibitors ( p = .0002), while those with missense mutations had a low risk ( p < .0001). Thirteen (29.5%) patients received immune tolerance induction (ITI) therapy using low‐dose prothrombin complex concentrate regimens. Twelve completed ITI with three (25.0%) achieving success. Nephrotic syndrome developed in two (16.7%) patients during ITI. Conclusion: This study reports the largest Chinese cohort of HB inhibitor patients. Large deletions were most significantly associated with inhibitor development. Low‐dose ITI might be feasible for FIX inhibitor eradication.